Islamic Republic of Afghanistan : Poverty Reduction Strategy Paper; Progress Report. (IMF Staff Country Reports; Country Report, 2008)
The Afghanistan National Development Strategy (ANDS) is Afghanistan's Poverty Reduction Strategy Paper (PRSP). Implementation of the ANDS is highly dependent on donor assistance. The main general objectives of the ANDS are to improve the quality of life of Afghan people and to reduce poverty. ANDS will play a key role in improving aid coordination and aid effectiveness. The first draft of the ANDS chapter on implementation, monitoring and evaluation and the policy paper on how to improve aid coordination and aid effectiveness has been prepared.